1985
DOI: 10.1148/radiology.156.2.4011892
|View full text |Cite
|
Sign up to set email alerts
|

Erosive arthritis in Cronkhite-Canada syndrome.

Abstract: A patient with Cronkhite-Canada syndrome and an erosive arthritis whose course correlated with the activity of his bowel disease is described. We found no previous description of articular manifestations in any patients with this syndrome. Cronkhite-Canada syndrome should be added to the differential diagnosis of erosive arthritis in the appropriate clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There has been only one reported case showing articular manifestation in CC patient in the past literature [20]. Sanders et al [20] reported a case of CC syndrome with erosive arthritis. The clinical course of arthritis was correlated with the activity of his bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…There has been only one reported case showing articular manifestation in CC patient in the past literature [20]. Sanders et al [20] reported a case of CC syndrome with erosive arthritis. The clinical course of arthritis was correlated with the activity of his bowel disease.…”
Section: Discussionmentioning
confidence: 99%